2020
DOI: 10.1021/acsomega.0c03581
|View full text |Cite
|
Sign up to set email alerts
|

GPR120 Agonist GW9508 Ameliorated Cellular Senescence Induced by ox-LDL

Abstract: Introduction Oxidized low-density lipoprotein (ox-LDL)-induced endothelial senescence is involved in the pathogenesis of atherosclerosis and many cardiovascular diseases. G-protein-coupled receptor 120 (GPR120), a type of orphan G-protein-coupled receptors (GPRs), plays a vital role in mediating anti-inflammatory and insulin-sensitizing effects. The biological function of GPR120 in vascular endothelial cells is largely unknown. Methods The human aortic endothelial cells (HAECs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 40 publications
(71 reference statements)
0
8
0
1
Order By: Relevance
“…RANKL keeps Nrf2 in the cytoplasm by increasing the expression of Keap1, which binds Nrf2 and prevents its translocation into the nucleus [ 10 ]. Liu et al have reported that the GPR120 agonist GW9508 can increase nuclear translocation of Nrf2 in human endothelial cells [ 28 ]. Similarly, we have shown in this present study that TUG-891 increased nuclear translocation of Nrf2 in RANKL-induced murine macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…RANKL keeps Nrf2 in the cytoplasm by increasing the expression of Keap1, which binds Nrf2 and prevents its translocation into the nucleus [ 10 ]. Liu et al have reported that the GPR120 agonist GW9508 can increase nuclear translocation of Nrf2 in human endothelial cells [ 28 ]. Similarly, we have shown in this present study that TUG-891 increased nuclear translocation of Nrf2 in RANKL-induced murine macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…GW9508 also decreased the expression of p53 and plasminogen activator inhibitor 1, two standard hallmarks of senescent cells. Mechanistically, GW9508 promotes oxLDL-related translocation of NF-E2-related factor 2 (NRF2) to the nucleus ( 68 ). Similarly, quercetin treatment also reduces oxLDL-induced endothelial cell senescence in HAECs ( 69 ).…”
Section: Oxldl and Endothelial Cell Dysfunctionmentioning
confidence: 99%
“…And LDL can easily be oxidized to ox-LDL which is an important feature of abnormal lipid metabolism [ 64 , 65 ]. While, ox-LDL is critical in the progress of atherosclerosis and non-alcoholic steatohepatitis [ 66 , 67 ]. Recently, studies have revealed the function of ox-LDL in the cancer cell proliferation [ 24 ], cell cycle [ 68 ], EMT [ 69 ], angiogenesis [ 70 ] and metastasis [ 71 ].…”
Section: Discussionmentioning
confidence: 99%